Academic SEO – increasing the visibility of research output - Schilhan, Lisa; Kaier, Christian (Septentrio Conference Series, 2019)
Watch the VIDEO. In times of an ever-increasing information overload, Academic Search Engine Optimization (ASEO) supports findability of relevant information and contributes to the FAIR principles. It enhances efficiency in literature and data search and therefore plays an increasing role in the research lifecycle. ASEO is an important aspect to consider when preparing a scientific manuscript for publication. Authors can increase the visibility of their papers in library catalogues, databases, repositories and search engines with simple measures like choosing informative author keywords. The more (meta-)data these search algorithms can use, the higher the probability that a data set or paper will show up in a result list. ASEO enables search algorithms and readers to quickly and unambiguously identify relevant content, thus also helping institutions to increase research visibility. In addition, authors and publishers share an interest in describing content in a way that makes it easy to find it. Librarians, with their extensive knowledge and wealth of experience in literature research and metadata management such as keyword assignment, can provide valuable advice on the role of as correct and complete metadata as possible and on suitable keywords for search algorithms. For this reason, the Publication Services at Graz University Library have recently started offering training and workshops for authors. The presentation will provide an introduction into strategies to enhance visibility and findability of online content, such as research articles, with some theoretical background as well as practical examples.